1996
DOI: 10.1203/00006450-199606000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of 3-Hydroxy-3-methylglutaryl-Coenzyme A Reductase Inhibitors on the Development of Myopathy in Young Rats

Abstract: HMG-CoA reductase inhibitors (statins), cholesterol-lowering drugs that have not been approved for use in children and adolescents, may cause myopathy as a side effect. We compared the effects of three statins (simva-, prava- and lovastatin) in young rats to determine whether skeletal muscle of young animals is more susceptible than that of adults. We also evaluated whether the type of statin (lipophilic versus hydrophilic) determines the degree of muscle damage. Administration via chow of simvastatin (15 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
32
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 45 publications
4
32
0
Order By: Relevance
“…In this study, we examined the effects of Cer on Ca 2+ release in skinned skeletal muscle fibers mainly from the mouse, which we used in our previous experiments. In some experiments, however, we also used rat skinned muscle fibers because statin-induced myopathy was reported in the rat (8,9). Our results demonstrated that Cer, a lipophilic type of statin, also had an ability to cause Ca 2+ release from the SR.…”
Section: +mentioning
confidence: 68%
“…In this study, we examined the effects of Cer on Ca 2+ release in skinned skeletal muscle fibers mainly from the mouse, which we used in our previous experiments. In some experiments, however, we also used rat skinned muscle fibers because statin-induced myopathy was reported in the rat (8,9). Our results demonstrated that Cer, a lipophilic type of statin, also had an ability to cause Ca 2+ release from the SR.…”
Section: +mentioning
confidence: 68%
“…Several reports have shown that statins may induce apoptosis in cultures of cortical neurons of both humans and rat glioma cells 18 -20 and myopathy in young rats. 21 However, a recent prospective study in humans found no relationship between exposure to Sim during pregnancy and adverse pregnancy outcome. 22 In our experiments, the neuroprotective effect of Sim occurred without significant toxic effects, because the reduction of body weight observed during treatment and at weaning was completely recovered in adults, and both spontaneous activity and cognitive abilities in Sim-treated control animals did not differ from those of control animals.…”
Section: Discussionmentioning
confidence: 99%
“…Rats, especially juveniles, are susceptible to statin-induced myotoxicity (Reijneveld et al, 1996;Westwood et al, 2005). However, because the rat liver responds to statins by increasing hepatic cholesterol synthesis, use of plasma cholesterol as an indication of statin efficacy precludes the rat from being an optimal model for estimating therapeutic safety margins (Krause and Newton, 1995).…”
mentioning
confidence: 99%